Macro Travel and Tours Enterprise / Nokkidzan Ahmad Mokhtar... [et al.] - Ahmad Mokhtar, Nokkidzan; Abu Bakar, Mohd Safaruddin; Lajis, Muzaffar; Abdul Wahab, Mohd Fadzil; Ahmad, Nasrul Aswady (2001)
The tourism and recreation industry has become an important activity in development of Malaysian's economy. Macrotravel and tours enterprise was located at Sungai Petani Kedah. It was a partnership business. Main activity of this company are providing a travel and tours services. It was started on 15 March 2004.